If and only if people were logical! The effect of pragmatic enrichment on reasoning with abstract and realistic materials - Blochowiak, Joanna (2022)
Human beings often fall prey to fallacious reasoning. One influential view holds that reasoners endorsing fallacies do not commit logical errors but rather that they endorse such fallacies on pragmatic grounds, i.e. by tacitly considering a conditional premise (If you wash my car, I will give you $10) a biconditional one (I will give you $10, if and only if you wash my car). If such an operation – known as invited inference or pragmatic enrichment – does occur, the acceptance of an invalid argument becomes legitimate. This paper seeks to find out if pragmatic enrichment happens for conditionals and, if so, under what circumstances. To address this issue, we conducted two complementary experiments in which we manipulated the type of material used in reasoning (abstract vs realistic) and the nature of the major premise (conditional vs biconditional). Our results indicate that both of these factors do indeed affect reasoning processes and performance. Overall, our findings suggest that only conditionals undergo pragmatic enrichment albeit not systematically as enrichment takes place only with a subclass of realistic materials.